The Regulation of Host Intestinal Microbiota by Polyphenols in the Development and Prevention of Chronic Kidney Disease - Bao, Naren; Chen, Fangjie; Dai, Di (Frontiers in Immunology, 2020)
Polyphenols are essential antioxidants in our regular diet and their chemical structure has shown potential antibacterial effects. Important biological activities, including antioxidant, anticancer or antibacterial activities have been found in some of the polyphenols. In recent years, the benefits of polyphenols on human health have attracted more and more attention from the scientific community. Recent studies have shown that polyphenols such as anthocyanin, catechin, chlorogenic acid and resveratrol can inhibit pathogenic bacteria such as Escherichia coli and Salmonella to regulate the intestinal microflora. The imbalance of intestinal microflora and the destruction of the intestinal barrier function have been proved to have a potential relationship with the occurrence of chronic kidney diseases (CKD). These can trigger the immune system to cause inflammations, increase the production of uremic toxins, and further worsen the condition of CKD. Therefore, the maintenance of intestinal microflora and the intestinal tract in a stable and healthy state may be able to immunize and treat CKD. The use of common antibiotics may lead to drug resistance of pathogens, and the beneficial effect of polyphenols may become a natural substitute for antibiotics. This paper reviews the effects of different polyphenols, such as anthocyanin, catechin, chlorogenic acid, resveratrol, on regulating intestinal microorganisms, inhibiting pathogenic bacteria, and improving inflammations. In addition, this paper also reviews the effects of different polyphenols which have been studied in recent years to reduce intestinal injury, intestinal inflammatory response, and improve related functional parameters of intestinal inflammatory diseases. In conclusion, polyphenols would be a potential source to modulate the intestinal microbiota, improve inflammatory response, and reduce kidney damage as well as to immunize or treat CKD.